2014
DOI: 10.1097/mph.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infections in Children With Cancer

Abstract: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infections (LRTIs) in children, especially those with cancer. Data on RSV infections in this vulnerable population is limited. We conducted a retrospective study of all RSV infections in children with cancer from 1998 to 2009 to determine characteristics and outcomes of these infections, identify risk factors for LRTI and mortality, and the effect of antiviral therapy on these outcomes. We identified 59 patients with a median age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…For example, a Spanish study by Mendoza Sánchez et al [ 17 ] retrospectively reviewed respiratory viral infections in children aged ≤14 years and found rates of RSV infection were twice as high in patients with HIV than those receiving chemotherapy for cancer (101 vs. 46 per 1000, respectively). For patients undergoing HSCT or SOT, RSV infections typically occur within the first 2 years following transplant [ 35 , 37 ]. Increased disease severity has been associated with prolonged shedding of RSV and with higher viral loads maintained for longer periods [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a Spanish study by Mendoza Sánchez et al [ 17 ] retrospectively reviewed respiratory viral infections in children aged ≤14 years and found rates of RSV infection were twice as high in patients with HIV than those receiving chemotherapy for cancer (101 vs. 46 per 1000, respectively). For patients undergoing HSCT or SOT, RSV infections typically occur within the first 2 years following transplant [ 35 , 37 ]. Increased disease severity has been associated with prolonged shedding of RSV and with higher viral loads maintained for longer periods [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Outbreaks of RSV have been reported to occur in cancer care outpatient departments where many pediatric patients with malignancy or those undergoing transplantation are managed [ 33 , 50 , 57 ]. In a retrospective study of all RSV infections in children with cancer from 1998 to 2009 at the MD Anderson Cancer Centre in Texas, Chemaly et al [ 37 ] found that, whilst the majority of cases (43/59; 73%) were community-acquired, over one-quarter (27%) were nosocomial. Since many HSCT and SOT recipients and children with malignancies are frequently seen in clinics, this could explain in part the high rates of RSV infection reported among this patient group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Among 57 patients, 37% experienced progression to lower respiratory tract disease. Three patients died of respiratory failure within 60 days of RSV diagnosis (1 had concomitant bacteremia and fungemia and 1 had concomitant herpes simplex pneumonia).…”
Section: Immunocompromised Childrenmentioning
confidence: 99%
“…Patients with hemato-oncological disease are at risk for severe RSV-caused infection -especially in the context of hematopoietic stem cell transplantation (HSCT) [6,7]. In the literature varying RSV-related case fatality rates are reported in children with cancer to range from 5% to 33% [8][9][10].…”
Section: Introductionmentioning
confidence: 99%